RACK-1 overexpression protects against goniothalamin-induced cell death - Inayat-Hussain, S.H. (Elsevier, 2009)
Goniothalamin, a styryllactone, has been shown to induce cytotoxicity via apoptosis in several tumor cell lines. In this study, we have examined the potential role of several genes, which were stably transfected into T-cell lines and which regulate apoptosis in different ways, on goniothalamin-induced cell death. Overexpression of full-length receptor for activated protein C-kinase 1 (RACK-1) and pc3n3, which up-regulates endogenous RACK-1, in both Jurkat and W7.2 T cells resulted in inhibition of goniothalamin-induced cell death as assessed by MTT and clonogenic assays. However, overexpression of rFau (antisense sequence to Finkel–Biskis–Reilly murine sarcoma virus-associated ubiquitously expressed gene) in W7.2 cells did not confer resistance to goniothalamin-induced cell death. Etoposide, a clinically used cytotoxic agent, was equipotent in causing cytotoxicity in all the stable transfectants. Assessment of DNA damage by Comet assay revealed goniothalamin-induced DNA strand breaks as early as 1 h in vector control but this effect was inhibited in RACK-1 and pc3n3 stably transfected W7.2 cells. This data demonstrate that RACK-1 plays a crucial role in regulating cell death signalling pathways induced by goniothalamin.